Energy aware flash flood monitoring stations using a GA-fuzzy logic control mechanism - Benya Suntaranont (2018)
© 2015 IEEE. Flash flood is a natural disaster that causes great losses; it happens mostly in rural areas. Heavy rainfall is gathered into the main river on watershed areas. Lots of water comes into the river. This causes a great volume of water flows down to the lower area of watershed. The great volume of water rapidly comes and goes. The flash flood watcher is required to notice the peak flow. An automatic water level monitoring station is a solution for keeping track of all flowing situations. In this research, a water level monitoring station has been invented and installed on a target area for flash flood early warning. The monitoring station periodically reports the water level through internet to a website and social networks (e.g., facebook and twitter). However, the power consumption of the monitoring station has become an issue since there is no electric power at the installation area. This research also proposed to automatically adjust the data transmission rate of the monitoring station to the environmental changes. Thus, the fuzzy logic control mechanism has been applied for searching for appropriate transmission rate in several flow periods. The appropriate of data transmission rate from fuzzy logic control mechanism are also optimized using a genetic algorithm. The results show that the monitoring stations work properly. They are able to continuously transmitted the sensing data to the base station with efficient power consumption.